Q: Solve 5t - 7 11

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Related questions

You don't for t, as gathering your coefficient variables together = 0 5t - 5 = 5t + 7 now, subtracting 5t from either side to get the variables on one side of the equation renders this. - 5 does not = 7

5t - 9 = 26(Add 9 to both sides)5t = 35(Divide both sides by 5)t = 7

no answer to t 5t - 5 = 5t +7 ( subtract 5t from both sides reducing to) -5 = +7 Negative 5 does not equal positive 7.

5t - 1 = -11 Therefore, 5t = -10 t = -10/5 t = -2

_t(5t squared t+)

If: 7+t = 11 Then: t = 11-7 So: t = 4

-8t+2

5

"Add" means "+" and "minus" means " - "; so we have:4p + 5t - p + 10tNow group the numbers with variables together:4p - p and 5t + 10t, and then simplify:3p + 15t

5t + 25 = 525 divide by 5 to both sides t + 5 = 105 subtract 5 to both sides t = 100

5y-4 = 7 5y = 7+4 = 11 y = 11 / 5 = 2.2

To calculate the result of 5t on a hf (Hartree-Fock) method, you would need to solve the Hartree-Fock equations to determine the electronic wavefunction and energy of the system with the kinetic energy operator represented by 5t. This involves iterative computations of the electron density until self-consistency is achieved. The final result would be the total energy of the system considering the 5t operator.